DETEKSI DINI KANKER SERVIKS DENGAN PEMERIKSAAN PAP SMEAR PADA WANITA PETANI TEMBAKAU DI KECAMATAN WULUHAN KABUPATEN JEMBER - Mashuri, Mashuri (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Universitas Jember, 2022)
The purpose of this study was to determine the prevalence of cervical precancerous lesions by conducting early detection of cervical cancer using Pap smear examination on tobacco farming women in Wuluhan District, Jember Regency. The design of this research is descriptive exploratory through the method of observational approach and using purposive sampling when selecting samples and found there are 52 respondents. The instrument of this study used an observation sheet for cervical cytology specimen examination with Papanicolaou staining and classification of cytological examination results based on the Papanicolaou classification and the Bethesda system, and the data were analyzed using the univariate test. The results of the analysis of Pap smears showed that 20 people had non-specific chronic inflammation, namely 38.4%, 14 people non-specific acute inflammation, namely 26.9%, Candida albicans fungal infection five people, namely 9.6%, Normal smear five people, namely 9.6%, Atrophic smear four people, namely 7.6%, Atrophic smear with non-specific acute inflammation two people, namely 3.8%, Atrophic smear with chronic non-specific inflammation one person,i.e., 1.9% Bacterial infection actinomyces sp one person that is 1.9% and based on the Papanicolaou classification and the Bethesda system, there were 47 people, namely 90.4% belonging to Papaniculaou class I (same as standard in the Bethesda system classification), four people, namely 7.6% in the Class II category (same as NILM in the Bethesda system classification) and there is one person, namely 1.9% in the class III category (same as LSIL in the Bethesda classification system) It has been recommended that women tobacco farmers who have a high risk of cervical cancer always pay attention to their reproductive health by carrying out regular Pap smear examinations for early detection to prevent and overcome cervical cancer as early as possible.